PENGEMBANGAN TES DIAGNOSTIK THREE-TIER MULTIPLE CHOICE UNTUK MENGUKUR KONSEPSI FISIKA SISWA SMA - Nurhayati Nurhayati; Syarif Lukman Hakim Al Sagaf; Wahyudi Wahyudi (Jurnal Pendidikan (Teori dan Praktik), 2019)
This study aims to determine the quality of diagnostic test questions with regular straight motion material. This research is a descriptive study using a quantitative approach. In this research, Sujek was a class X student at Jagoi Babang 01 High School. The research instrument was in the form of question feasibility questionnaire addressed to the validator and the test used to test the characteristics of the questions including validity, reliability, level of difficulty and differentiating power of the questions and knowing the profile of students' conceptual understanding. The results of the study indicate that: (1) A total of 13 questions have very good assessment criteria by experts; (2) 9 questions are declared valid and 3 questions are invalid; (3) Reliability index of 0.81 with very strong criteria; (4) 11 questions have medium criteria and 1 problem is difficult keriteria; (5) criteria for distinguishing good as many as 4 questions, criteria are enough 6 questions and bad criteria 2 questions; (6) The percentage of students who understand the concept is 22.31%, misconceptions are 36.56% and do not understand the concept of 41.13%.